Trastuzumab Sensitizes Ovarian Cancer Cells to EGFR-targeted Therapeutics - Wilken Jason A; Webster Kristy T; Maihle Nita J (BMC, 2010)
Abstract Background Early studies have demonstrated comparable levels of HER2/ErbB2 expression in both breast and ovarian cancer. Trastuzumab (Herceptin), a therapeutic monoclonal antibody directed against HER2, is FDA-approved for the treatment of both early and late stage breast cancer. However, clinical studies of trastuzumab in epithelial ovarian cancer (EOC) patients have not met the same level of success. Surprisingly, however, no reports have examined either the basis for primary trastuzumab resistance in ovarian cancer or potential ways of salvaging trastuzumab as a potential ovarian cancer therapeutic. Methods An in vitro model of primary trastuzumab-resistant ovarian cancer was created by long-term culture of HER2-positive ovarian carcinoma-derived cell lines with trastuzumab. Trastuzumab treated vs. untreated parental cells were compared for HER receptor expression, trastuzumab sensitivity, and sensitivity to other HER-targeted therapeutics. Results In contrast to widely held assumptions, here we show that ovarian cancer cells that are not growth inhibited by trastuzumab are still responsive to trastuzumab. Specifically, we show that responsiveness to alternative HER-targeted inhibitors, such as gefitinib and cetuximab, is dramatically potentiated by long-term trastuzumab treatment of ovarian cancer cells. HER2-positive ovarian carcinoma-derived cells are, therefore, not "unresponsive" to trastuzumab as previously assumed, even when they not growth inhibited by this drug. Conclusions Given the recent success of EGFR-targeted therapeutics for the treatment of other solid tumors, and the well-established safety profile of trastuzumab, results presented here provide a rationale for re-evaluation of trastuzumab as an experimental ovarian cancer therapeutic, either in concert with, or perhaps as a "primer" for EGFR-targeted therapeutics.